Synthesis and Characterization of MnO2, Mn3O4, NiO and Cd Doped ZnO Nanoparticles via a PEG Assisted Route - Lashanizadegan, Maryam; Mirzazadeh, Hoda (Asian Journal of Chemistry, 2012)
MnO2, Mn3O4, NiO and Cd doped ZnO nano structures have been synthesized by PEG assisted process. The effect of amount of polymer, calcination and temperature on the formation of these nano structures has been investigated. It is observed that these factors play vital role on the growth of nanostructures. The products were characterized by X-ray diffraction (XRD), IR, optical absorption measurement (UV/VIS), scanning electron microscopy (SEM) and EDAX.